Trends of spruce forests’ decline in the Ukrainian Carpathians: Case study in the wet mezotrophic common beech – silver fir – Norway spruce forest type - Shparyk, Y. S.; Parpan, T. V. (Forestry and Forest Melioration, 2020)
Introduction Regional decline of the Norway spruce (Picea abies (L.) Karst.) forests in the Ukrainian Carpathians has been observed for over 10 years. Many scientific results have already been obtained: the causes of that large spruce decline are significant (climatic) changes in the site conditions. Moreover, spruce decline will change the main species in the regional forests from Norway spruce to common beech or silver fir, but it will not result in the forest area loss. The economic and social impacts of spruce decline will be the most unfortunate. The most effective forestry measure aimed at mitigating the spruce decline consequences is sanitary felling. Furthermore, the spruce decline forecasts indicate a significant loss of spruce wood volume and forest area in the next 20 years. At that, there is still no clear understanding of forest layers dynamics in the declining forests within forest types. The aim of the research was to determine the trends of forest indicators dynamics within forest layers due to the spruce declining with the most common regional forest type as a case study to optimize and ground forestry measures here. Materials and Methods The main research was conducted on the permanent research plot Vy-1-10 established in 2010, the further inventories took place in 2014 and 2019. The plot is situated in the Vygoda Forestry State Enterprises within wet mesotrophic Common beech – Silver fir – Norway spruce forest type. It was mature (115 years) fir (20% of its wood volume) – spruce (80%) forest stand with some trees of Sycamore and Silver birch (by 2008) (secondary stand). Its growth was a little lower than normal (II growth class), so was its basal area (relative index – 0.66). The study results obtained on the other three plots in this forest type were used to verify the data from plot Vy-1-10. The generally accepted forestry research methods with elements of the IUFRO methodologies were applied within the research. Results Spruce decline in the wet mesotrophic Common beech – Silver fir – Norway spruce forest type results in a decrease of the tree quantity, the spruce basal area and wood volume. However, other forest stand indicators do not have the same trends. Knowing species composition is very important when taking decisions on forestry management. The dynamics of species composition in the studied stands is clear, namely 5 % per year decrease in spruce and the same increase in fir. The trees number dynamics is different by stand layers: in the first layer it is constantly decreasing and in the second one and especially in the third one it is increasing. The wood volume dynamics of living trees had similar trends: in the first layer it was constantly decreasing (?4 % per year) and in the second (?2 %) and especially in the third (?16 %) layers it was increasing. Indicators of the trees that dry first were determined as follows: species – spruce, layer – first, vitality – low. The dynamics of lying deadwood volume had a rapid increase from 2010 to 2014 and then – a slight decrease till 2019, which corresponds to the wood volume dynamics of the living trees. Furthermore, natural regeneration number has been increasing throughout the study period, and new species (beech and birch) appeared here. Grass cover biodiversity has increased by seven new species, undergrowth (shrubs) has hardly changed, and forest litter depth decreased from 2.5 to 1.5 cm. Conclusions Forestry management in the declining spruce forests within this forest type should be based on the following: healthy spruce trees should be protected from damage; secondary spruce forest transition into native stands without human intervention (cutting) takes 15–20 years; tending is not needed in young spruce forests; dry tree cutting should be done in the current year (optimally – next month after drying); lying deadwood (or its bark) must be removed from the forest in the current year; a considerable number of natural regeneration prevents artificial reforestation. 3 Figs., 3 Tables, 21 Refs. Key words: Norway spruce, decline stages, forest type, stand layer, lying deadwood, natural regeneration, grass cover.